Differential Patterns of Children's Knowledge of Quantifier Meaning Revealed Under Different Tasks - Shetreet, Einat; Novogrodsky, Rama (Frontiers in Communication, 2019)
This study examines children’s comprehension of quantifiers in Hebrew, using several tasks. We focused on a linguistic ambiguity related to universal quantifiers that express a distinction between collectivity and distributivity: all can be assigned with both a collective reading and a distributive reading (“a flower for all fairies” can be interpreted as an event with one flower or an event with multiple flowers), whereas each has a distributive reading only (“a flower for each fairy” is an event with multiple flowers). Unlike English, Hebrew has a single universal quantifier and thus, it expresses the collectivity/distributivity distinction using two morphosyntactic forms: one form (kol+ definite plural noun) is equivalent to all and has the two readings, and the other form (kol+ indefinite singular noun) is equivalent to each and has only one reading. We examined how Hebrew-speaking preschoolers (4-6 years) understand sentences in the two forms, and how they resolve the ambiguity of the ambiguous form, while focusing on the type and presence of contrast in three preference tasks: Experiment 1 used a conventional picture-matching task where the collective and distributive meanings were contrasted using two pictures (meaning contrast); Experiment 2 used a sentence-matching task where the two morphosyntactic forms were contrasted using two sentences (linguistic contrast); and Experiment 3 used a novel drawing task including instructions in one form (no contrast). In all tasks, adults showed a consistent response pattern, matching the ambiguous form (equivalent to all) to the collective reading and the distributive form (equivalent to each) to the distributive reading. Children, on the other hand, were extremely affected by the task, showing adult-like performance pattern in the picture-matching task, but not in the other tasks. This suggests that children can distinguish between the two morphosyntactic forms, but they do not fully attain adults’ preference pattern. The differences between the tasks can be attributed to the salience of the contrast, task experience, or working memory. The results highlight the need for a careful selection of language tasks both in basic research and in clinical assessment.